O uso do agrotóxico: o caso do cultivo de abacaxi no município de Sapé PB. - Santos, Julliane Crispiniano dos. (2014)
Agrotoxin are chemical goods, used to control pests and diseases in agriculture. However its use have been caused serious risks to health of rural workers, consumers and also to environment. Brazil is the largest consumer of agrotoxin around the world, this use in large scale have been led the country to a high and alarming contamination. It is important identify the factors of risks of rural workers, avoiding its vulnerability to agrotoxin with the use of individual protection equipment – IPE, and with instruction about the use of chemical products. This work has the objective of evaluate and elucidate the use of agrochemicals, informing the serious damages that they cause to population, and thy main form of manifestation. So, is entirely necessary to prevent of the harmful effects of agrotoxins that can even cause death.